2015
DOI: 10.1002/mds.26279
|View full text |Cite
|
Sign up to set email alerts
|

GDNF gene is associated with tourette syndrome in a family study

Abstract: Background Tourette syndrome is a disorder characterized by persistent motor and vocal tics, and frequently accompanied by the comorbidities attention deficit hyperactivity disorder and obsessive-compulsive disorder. Impaired synaptic neurotransmission has been implicated in its pathogenesis. Our aim was to investigate the association of 28 candidate genes, including genes related to synaptic neurotransmission and neurotrophic factors, with Tourette syndrome. Methods We genotyped 506 polymorphisms in a disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…(d) 12 TS GWAS-based top SNPs, i.e., the top 5 LD-independent SNPs from the first GWAS of TS [ 6 ], 4 top SNPs from the Gilles de la Tourette Syndrome Genome-Wide Association Study Replication Initiative [ 7 ], and the top 3 SNPs from the first cross-disorder GWAS of TS and OCD [ 20 ]; and (e) 17 top SNPs from GWAS studies of OCD [ 21 ], ADHD [ 22 , 23 ], and ASD [ 24 , 25 ]. We did not include the previously implicated TS SNPs rs1894236 ( HDC ), rs1056534 ( TBCD ), rs25531 ( SLC6A4 ), rs25532 ( SLC6A4 ), nor tSNPs covering the possible TS candidate genes DRD4 , Arylacetamide Deacetylase ( AADAC ) [ 26 , 27 ], and Glial Cell Derived Neurotrophic Factor ( GDNF ) [ 27 ], nor 19 SNPs recently implicated in a meta-analysis of TS and ADHD [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…(d) 12 TS GWAS-based top SNPs, i.e., the top 5 LD-independent SNPs from the first GWAS of TS [ 6 ], 4 top SNPs from the Gilles de la Tourette Syndrome Genome-Wide Association Study Replication Initiative [ 7 ], and the top 3 SNPs from the first cross-disorder GWAS of TS and OCD [ 20 ]; and (e) 17 top SNPs from GWAS studies of OCD [ 21 ], ADHD [ 22 , 23 ], and ASD [ 24 , 25 ]. We did not include the previously implicated TS SNPs rs1894236 ( HDC ), rs1056534 ( TBCD ), rs25531 ( SLC6A4 ), rs25532 ( SLC6A4 ), nor tSNPs covering the possible TS candidate genes DRD4 , Arylacetamide Deacetylase ( AADAC ) [ 26 , 27 ], and Glial Cell Derived Neurotrophic Factor ( GDNF ) [ 27 ], nor 19 SNPs recently implicated in a meta-analysis of TS and ADHD [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…These include dopaminergic neurotransmission (9,10) as well as glutaminergic (11,12), serotoninergic (13), GABA-ergic (14)(15)(16), or endocannabinoid (17,18) neurotransmission. In addition, a significant number of genetic variants have also been identified [SLITRK1 (19)(20)(21), DRD2 (22), DRD3 (23), AADAC (24), ADORA (25), BTBD9 (26), CNR1 (18), GDNF (27), KCNJ5 (28), IL1RN (29), PNKD (30), and HDC (31,32), to give only some examples]. The first genome-wide association study (GWAS) (33) in GTS demonstrated a combined genetic background for GTS and OCD.…”
Section: Toward the Definition Of Treatment Refractoriness In Gts Lesmentioning
confidence: 99%
“…Most individuals, upwards of 45%–60%, are also affected by a co-morbidity such as obsessive compulsive disorder (OCD), attention deficit hyperactivity disorder (ADHD), depression, or autism[ 1 ]. Although the disorders originating from TS sometimes lessen with age, the co-morbid symptoms may continue until adolescence and even adulthood [ 2 , 3 ]. Therefore, the occurrence of multiple conditions may present a challenge to the complicated pathogenesis of TS.…”
Section: Introductionmentioning
confidence: 99%